2013
DOI: 10.5087/dad.2013.211
|View full text |Cite
|
Sign up to set email alerts
|

Annotation upon Annotation: Adding Signalling Information to a Corpus of Discourse Relations

Abstract: We present an annotation effort that involves adding a new layer of annotation to an existing corpus. We are interested in how rhetorical relations are signalled in discourse, and thus begin with a corpus already annotated for rhetorical relations, to which we add signalling information. We show that a very large number of relations carry signals that identify them as such. The detailed, extensive analysis of signals in the corpus will aid research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 64 publications
(83 reference statements)
4
34
0
5
Order By: Relevance
“…We have as of yet not been able to find or compile another translation corpus on which we can replicate this study. However, in as far as the data are comparable, the patterns in the marking of coherence relations found in the current study are very similar to patterns reported on the basis of the PDTB (Asr and Demberg, 2012) and the RST Treebank (Taboada and Das, 2013), both of which use newspaper texts from the Wall Street Journal.…”
Section: Parametersupporting
confidence: 90%
“…We have as of yet not been able to find or compile another translation corpus on which we can replicate this study. However, in as far as the data are comparable, the patterns in the marking of coherence relations found in the current study are very similar to patterns reported on the basis of the PDTB (Asr and Demberg, 2012) and the RST Treebank (Taboada and Das, 2013), both of which use newspaper texts from the Wall Street Journal.…”
Section: Parametersupporting
confidence: 90%
“…Also, new features may be explored, such as various types of discourse signals (beyond discourse markers) proposed by [29] and the use of semantic knowledge, such as polarity and synonymy.…”
Section: Discussionmentioning
confidence: 99%
“…The extracted cue phrases are then used to infer the type of rhetorical relation. For this task we utilize a predefined list of rhetorical cue words adapted from the work of Taboada and Das (2013), which assigns them to the relation that they most likely trigger. For example, the transformation rule in Figure 2 spec-ifies that "although" is the cue word here, which is mapped to a "Contrast" relationship.…”
Section: Transformation Stagementioning
confidence: 99%